Parasitosis intestinales y su relacion con factores socioeconómicos y condiciones de habitat en niños de Neuquén, Patagonia, Argentina - Soriano, Silvia V. (2005)
The prevalence and distribution of intestinal parasites (IP) were investigated in children from two populations of different socioeconomic level, located in the same area of the city of Neuquén, in order to evaluate their relationship with habitat conditions and socioeconomic factors. Serial samples of faeces and anal scraping of 126 children between 2 and 14 years from two sectors of the suburban area of Neuquen (Sector I and Sector II) were analyzed. Data concerning habitat conditions and socioeconomic parameters were obtained by home visits and an observational structured survey. Presence of IP was detected in 50.7% of children from Sector I (suburban neighborhood with adequate sanitary conditions and middle or middle low socioeconomic level) and in 92.9% from children of Sector II (marginal settlement with poor sanitary conditions and low socioeconomic status). Seven intestinal protozoan and 4 helminth species were identified. Blastocystis hominis was the most frequent species found in both populations. No helminths different from Enterobius vermicularis were found in Sector I and the prevalence of such species was very low in Sector II. Deficient habitat conditions and low socioeconomic parameters showed relation with a higher prevalence of IP of direct transmission as protozoan and E.vermicularis in the studied populations. Nevertheless, even in this context favourable to transmission, the parasitic species which require intermediate stages of development in soil, don’t find an adequate habitat for dissemination in this region.